GROWTH SUPPRESSION OF LEGUMES IN PYRIPROXYFEN STRESSED SOILS: A COMPARATIVE STUDY - Ahemad, Munees (Emirates Journal of Food and Agriculture, 2013)
Insecticides are commonly used to combat economically important insect pests in agriculture. These plant-protecting agents severely decline crop productivity by affecting different plant growth parameters. The assessment of phytotoxicity of insecticides are generally, confined to one plant species and broad studies concomitantly evaluating the insecticide effect on more than one crop specifically, the legume are scarce. Hence, this study was designed to assess the effect of technical grade insecticide, pyriproxyfen simultaneously on legumes like chickpea, pea, lentil and greengram. Pyriproxyfen showed the highest toxicity to root and shoot dry biomass, leghaemoglobin, chlorophyll content and seed protein in chickpea, nodule numbers in pea, shoot nitrogen and root phosphorus in greengram, and nodule biomass, root nitrogen, root phosphorus, shoot phosphorus and seed yield in lentil. For instance, pyriproxyfen decreased the number of nodules (percent decline over controls) in each legume in an order: pea (44) > greengram (14) > chickpea (5) = lentil (5). Similarly, pyriproxyfen mediated percent decline in leghaemoglobin occurred in the order like: chickpea (69) > lentil (25) > pea (18) > greengram (12). Generally, pyriproxyfen affected most adversely the growth of both chickpea and lentil. It is concluded that the extent of phyto-toxicity of insecticide and the type of plant organs affected might differ among plant species.